Investigation of wheat straw gasification in CO2 atmosphere via thermogravimetric analysis - ÖZVEREN, UĞUR (My University, 2021)
Due to the depletion and adverse effects to the environment and the health of living things of fossil fuels, the orientation to alternative renewable energy sources has become an increasingly important issue worldwide. Biomass, as a renewable, is the most used energy resource after fossil fuels and can be found in various forms such as agricultural crops, forest wastes, animal residues, and municipal solid wastes in the environment. Gasification of biomass, that is obtained from thermochemical processing of biomass, is very attractive method for energy sustainability. Gasification process offers a promising way to remove carbon dioxide emissions from the atmosphere and utilize biomass effectively for energy production. In this study, wheat straw gasification process was investigated by using the thermogravimetric analysis (TGA). CO2 (Carbon dioxide) atmosphere was used as a gasifying agent to investigate the gasification behavior. The kinetics of the wheat straw gasification was studied by Coats Redfern method which is based on Kissinger method. Results obtained from the study provided a good agreement with the literature.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); Biomass; Coats-Redfern Method; Gasification Process; TGA